Measurement of the differential branching fraction of the decay Λ0b → Λμ+μ− - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physics letters, 2013)
The differential branching fraction of the decay Λb0→Λμ+μ− is measured as a function of the square of the dimuon invariant mass, q2. A yield of 78±12 Λb0→Λμ+μ− decays is observed using data, corresponding to an integrated luminosity of 1.0 fb−1, collected by the LHCb experiment at a centre-of-mass energy of 7 TeV. A significant signal is found in the q2 region above the square of the J/ψ mass, while at lower-q2 values upper limits are set on the differential branching fraction. Integrating the differential branching fraction over q2, while excluding the J/ψ and ψ(2S) regions, gives a branching fraction of B(Λb0→Λμ+μ−)=(0.96±0.16(stat)±0.13(syst)±0.21(norm))×10−6, where the uncertainties are statistical, systematic and due to the normalisation mode, Λb0→J/ψΛ, respectively.
Im Titel sind "0", "+" und "-" hochgestellt und "b" tiefgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 616
Gesehen am 21.04.2021